2013
DOI: 10.1200/jco.2013.31.15_suppl.4018
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation status-stratified randomized phase II trial of GEMOX with and without cetuximab in advanced biliary tract cancer (ABTC): The TCOG T1210 trial.

Abstract: 4018 Background: Gemcitabine/platinum combination is considered as globally acceptable standard care in patients with ABTC. Two recently published randomized trials showed adding EGFR antagonist, either erlotinib or cetuximab, does not further improve the clinical outcomes of gemcitabine/oxaliplatin (GEMOX)-treated ABTC patients. However, the impact of KRAS mutation status on the results of both studies was not properly addressed. Methods: A prospective, multicenter randomized, phase II trial to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
3
7
2
Order By: Relevance
“…Furthermore, our results did not differ in a predefined subset analysis according to the primary site of disease (ie, gallbladder vs non-gallbladder). Although we should be cautious when comparing trials, our results in both treatment groups are close to those reported with the combination of gemcitabine and cisplatin in the UKABC-02 trial 3 or the combination of gemcitabine and cisplatin with erlotinib 24 or cetuximab 25 in the two Asian trials (table 5). Indeed, our results did not confirm the promising efficacy data obtained with gemcitabine and oxaliplatin plus cetuximab in a phase 2 study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Furthermore, our results did not differ in a predefined subset analysis according to the primary site of disease (ie, gallbladder vs non-gallbladder). Although we should be cautious when comparing trials, our results in both treatment groups are close to those reported with the combination of gemcitabine and cisplatin in the UKABC-02 trial 3 or the combination of gemcitabine and cisplatin with erlotinib 24 or cetuximab 25 in the two Asian trials (table 5). Indeed, our results did not confirm the promising efficacy data obtained with gemcitabine and oxaliplatin plus cetuximab in a phase 2 study.…”
Section: Discussionsupporting
confidence: 82%
“…Our negative results could be partly explained by the results noted in the chemotherapy alone group, which were better than in those reported in the two Asian randomised trials of chemotherapy plus erlotinib 24 or cetuximab 25 (table 5). Although overall survival was not statistically different between treatment groups in any of these trials, a marginally significant progression-free survival benefit was reported with the addition of erlotinib (p=0·087) 24 or cetuximab (p=0·064) 25 to chemotherapy (table 5). Differences in sensitivity to chemotherapy between Asian and European populations might explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations